2020
DOI: 10.1186/s12967-020-02651-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic accuracy of a new point-of-care rapid test for SARS-CoV-2 virus detection

Abstract: Background The easy access to a quick diagnosis of coronavirus disease 2019 (COVID-19) is a key point to improve the management of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and to contain its spread. Up to now, laboratory real-time PCR is the standard of care, but requires a fully equipped laboratory and significant infrastructure. Consequently, new diagnostic tools are required. Methods In the present work, the diagnostic accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Furthermore, we assessed the influence of swab transport medium on rRT-PCR performance, demonstrating that the limit of viral detection is highly affected by the use of saline solution storage medium compared to universal transport medium (UTM), as previously reported by other competitors ( 7 ). We showed that Hyris bKIT Virus Finder COVID-19 assays provide an efficiency similar to that of the comparator without risks of cross-reaction effects or false-negative results, supporting sensitivity parameters described during preliminary studies ( 10 , 11 ). Importantly, the simplicity and diagnostic quality standards of the bKIT Virus Finder COVID-19 make the Hyris system ideal for a SARS-CoV-2 rapid diagnosis.…”
Section: Introductionsupporting
confidence: 78%
“…Furthermore, we assessed the influence of swab transport medium on rRT-PCR performance, demonstrating that the limit of viral detection is highly affected by the use of saline solution storage medium compared to universal transport medium (UTM), as previously reported by other competitors ( 7 ). We showed that Hyris bKIT Virus Finder COVID-19 assays provide an efficiency similar to that of the comparator without risks of cross-reaction effects or false-negative results, supporting sensitivity parameters described during preliminary studies ( 10 , 11 ). Importantly, the simplicity and diagnostic quality standards of the bKIT Virus Finder COVID-19 make the Hyris system ideal for a SARS-CoV-2 rapid diagnosis.…”
Section: Introductionsupporting
confidence: 78%
“…In addition, it benefits Low-income areas or communities that cannot provide POCT devices and extended testing [28] , [29] , [30] , [31] . The global pandemic has exposed apparent discrepancies in POCT techniques, and the significance of the development for preventing pandemics at their initial stage is highlighted [32] , [33] , [34] , [35] . In this review, we summarize related studies concerning POCT platforms.…”
Section: Overview Of Rapid Diagnosis By Poct Platformsmentioning
confidence: 99%
“… 1 RT-PCR RNA (Nasopharyngeal swab) 140 RdRp, N 10 copies/ reaction 30 100% 99% Yes [94] RT-PCR RNA (Nasopharyngeal swab) N.A. RdRp, E, N 5 copies/µL 60 100% 100% Yes [35] dd-PCR RNA (Nasopharyngeal swab) 11 ORF1ab 2 copies/ reaction 300 91% 100% Yes [40] RT-LAMP RNA (Nasopharyngeal swab) 2 M/N 20 copies/μL 13 100% 100% Yes [42] RT-LAMP RNA (Nasopharyngeal swab) 1.8 N, S, RdRp 118.6 copies/ reaction 20 94% 90% Yes [45] RT-LAMP RNA (Throat swabs) 20 ORF1a/b,S, N 20 copies/ reaction 30 100% 100% Yes [43] RCA RNA (Human blood) 1 N 4.9 copies/µL 61 89.2% 100% Yes [54] RPA RNA (swabs) 1 RdRp, N, E 6.9 ± 5.3 copies/µL 30 92.6% 98.9% Yes …”
Section: Poct Platforms Based On Other Technologiesmentioning
confidence: 99%
“…Hyris System TM provides more or less same results as RT-PCR method. It is a complete portable suite, which is versatile, fast, and reliable [30,31]. The main advantage of this test is it is fully automatic.…”
Section: The Hyris System Tm Covid-19 Diagnostic Kit Developed In Italymentioning
confidence: 99%